2019
DOI: 10.3390/photonics6020055
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Mid-Infrared Optical Frequency Comb Generation in Chalcogenide As2S3 Microbubble Resonators

Abstract: Mid-infrared optical frequency comb generation in whispering gallery mode microresonators attracts significant interest. Chalcogenide glass microresonators are good candidates for operating in the mid-infrared range. We present the first theoretical analysis of optical frequency comb generation in As2S3 microbubble resonators in the 3–4 μm range. The regime of dissipative soliton plus dispersive wave generation is simulated numerically in the frame of the Lugiato–Lefever equation. Using microbubble geometry al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The nonlinear Kerr coefficients found for different radii are plotted in Figure 2(b). The nonlinear dynamics of an intracavity field leading to OFC generation was simulated numerically in the framework of the LLE [6,32] as in [28,33] using home-made software based on the Split-step Fourier method. We used the master equation in the following form [6,29,34]:…”
Section: Resultsmentioning
confidence: 99%
“…The nonlinear Kerr coefficients found for different radii are plotted in Figure 2(b). The nonlinear dynamics of an intracavity field leading to OFC generation was simulated numerically in the framework of the LLE [6,32] as in [28,33] using home-made software based on the Split-step Fourier method. We used the master equation in the following form [6,29,34]:…”
Section: Resultsmentioning
confidence: 99%
“…Although the microcombs generated are multi-soliton state, the dual-comb spectroscopy could still acquire spectra of acetone at 127 GHz (4.2 cm −1 ) resolution. They further demonstrated high-throughput label-free MIR dual-comb [135]. The spectral range of the Kerr microcombs could span more than 700 nm.…”
Section: Kerr Microcombs Generationmentioning
confidence: 99%
“…Solitons possess highly attractive features for practical implementation beyond controlled environments due to their compacted dimensions and minimal requirements of energy. It was shown that the equilibrium between the cavity losses, cavity gain, group velocity dispersion (GVD), and Kerr nonlinearity can be maintained to create low-noise, coherent, broad-frequency combs in microresonators [4,10].…”
Section: Introductionmentioning
confidence: 99%